POTENSI PENGEMBANGAN BADAN USAHA MILIK KAMPUNGWOGEKEL, DISTRIK ILWAYAB, KABUPATEN MERAUKE - hendricus Lembang; sebestina siman (Musamus Journal of Economics Development, 2018)
The village has the authority to manage the existing potential for public welfare. So that the village government can form economic institutions, namely Village Owned Enterprises (BUMK). Kampung Wogekel has marine and swamp fisheries resources. The study uses a PRA approach based on community participation with SWOT analysis. The results of this study found: Strength Aspects namely 1). Sufficient labor is available, 2). The productive age potential of coastal communities, 3). Natural resources are very available, 4). Public facilities such as ports, Pertamina logistics, banking institutions, 5). Fishing boats belonging to the village. Weakness aspects are: 1). Weak capital, 2). Fisheries business technology is still simple, 3). Electricity, ice factories and shelters and storage vessels, 4). Limited access to marketing, 5). Community culture that does not have entrepreneurial spirit. Opportunity Aspect: 1). Job opportunities, 2). Natural resources have not been fully utilized, 3). Authority to establish BUMK, 4). Government support. Threat aspects, namely: 1) Low fish prices, 2). Weather and bad season, 3). There is still massive fishing to only take bubbles and also illegal fishing, 4). Central government regulation of the moratorium has not been revoked. So that the potential business sector is a fish shelter business. While alternative businesses are salted fish, coarse salt, nine household basic needs, tubers and crabs. Keywords: Development, economic institutions, entrepreneurship